The 20th Century’s Investigations of St. Thomas Aquinas’s Theory of Human Freedom (II) - Šulcienė, Lina (Problemos, 2001)
This is the second part of the article which reviews the XXth century’s studies of St. Thomas Aquinas’s theory of human freedom. The author analyses the studies of D. O. Lattin, B. Lonergan and other authors maintaining that there was the change in Aquinas’s thinking on the question of human freedom. Special attention is paid to the studies of the problem of the relation of man’s will to his ultimate end or the problem of the limits of human freedom.